Sustaining a federation of Future Internet experimental facilities - Jan Van Ooteghem; Steve Taylor; Paul Grace; Felicia Lobillo; Mikhail Smirnov; Piet Demeester (International Telecommunications Society (ITS), 2014)
The growing complexity of the Future Internet landscape has driven the need for large-scale federations of experimental testbeds that support the next generation of research and experimentation. However, such facilities are typically difficult to sustain in the long term, particularly in the transition from a publically funded development to a self-sustaining operation. Fed4FIRE is a cross-domain federation of Future Internet testbeds that seeks to lower the barrier to complex experimentation. This paper explores the Fed4FIRE sustainability plan in further detail, and first documents how our value proposition was elicited from key stakeholder requirement analysis. We examine and analyse further the potential service portfolio to be offered and operated by the federator, making use of a service management approach, and how this applies to the viability of potential federation business scenarios and their impact on all involved stakeholders in the long term. A plausible scenario is then proposed and evaluated. Finally we present some conclusions.
Keywords: 330; Sustainability; Value proposition; Federation; Experimentation; FIRE